The constitutional features of anatomy of the urethrovesical segment - Yu. Yu. Vinnik; V. G. Nikolaev (Сеченовский вестник, 2011)
The purpose of this study was to identify anatomic variations of the structure of urethrovesical segment in young men. Seized 60 urethrovesical segment the corpses of young men belonging to diﬀerent somatotype. Carried out an anthropometric survey of men and makroanatomic study urethrovesical segment. The results obtained demonstrated the constitutional structure of the urethrovesical segment dependence in young men.